Литературная норма в языке СМИ - Наталия Николаева (Studia Rossica Posnaniensia)
This article shows the latest trends related to expanding the vocabulary used by the media. Particular attention is paid to the assimilation of borrowings and errors into this language as well as the issue of using obscene vocabulary.